The Effects of Aerobic Training and Moringa oleifera on High-Density Lipoprotein and Cardiac Endurance among Males: Cardiac Endurance and Moringa oleifera Effects - Ali, Muhammad Safdar; Ahmed, Naseer; Marwat, Mohibullah Khan (Pakistan Journal of Health Sciences, 2025)
Aerobic training is a form of physical workout in which heart and lungs work efficiently to supply oxygen to the muscles for improving athletic performance. Objective: To investigate the effect of moderate aerobic training and Moringa oleifera leaf powder (MOLP) on high-density lipoprotein (HDL) and cardiac endurance among males. Methods: One hundred (100) male volunteers of age group 38.9 ± 6.7 years were randomly and divided into four groups i.e. the control group (T0), the moringa group (T1), the aerobic group (T2), and the Combined Group (T3). Moringa oleifera leaf powder (3 gm) was given to the T1 and T3 daily for five days a week for 12 weeks, while the T0 continued a normal diet routine. Results: Results indicate an increase in HDL posttest mean values of three interventional groups T1 (41.80 ±4.81 mg/dl), T2 (42.08 ± 1.28 mg/dl) and T3 (43.40 ±1.77 mg/dl) as compared to control group T0 (36.28 ±1.86 mg/dl). Beep tests mean values of the post-test of interventional groups T1 (10.1 ±1.24), T2 (10.2 ± 1.25) and T3 (12.0 ± 1 .18) and control group T0 (7.3 ± .67) were recorded. Conclusions: It was concluded that moderate aerobic training and MOLP have a positive effect on HDL and cardiac endurance among the interventional groups (T1, T2, and T3), with more significant improvement in T3 and no improvement in the control group.